KEANEKARAGAMAN JENIS LIKEN SEBAGAI BIOINDIKATOR PENCEMARAN UDARA DI AREA PABRIK PEMECAH BATU DESA SIDOMULYO - Bayuda Luqman Al-Farisi; Didin Ari Aprilia (Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2026)
Lichen is an indicator plant that is sensitive to air pollution, because this organism is accumulator and very adaptive to environmental changes. The purpose of this study was to find out what species are found in the stone crusher factory area and to determine the level of lichen diversity in the stone crusher factory area and its indication as air pollution bioindicator. This research uses a quatitative approach with line transect method. Sampling was carried out using purposive sampling technique. The result of the research carried out obtained 4 species of lichen with a total of 121 individuals. There are 4 species of lichen found in the stone crusher factory area, namely Flavoparmelia caperata, Diorygma poitaei, Graphis scripta, and Cryptothecia striata. The most found species is Flavoparmelia caperata species with a total of 66 individuals. Meanwhile, the fewest lichen species are the Cryptothecia striata species with 9 individuals. The level of lichen diversity in the stone crushing factory area based on Shannon-Wiener is classified as moderate, namely H’ 1,14.